2018
DOI: 10.1371/journal.pone.0191774
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effect of motor cortex stimulation in patients suffering from chronic neuropathic pain: An observational study

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…Risk of bias as assessed by the RoB2 showed that all included papers had a low overall risk-of-bias judgement 47,[75][76][77] . Risk of bias as assessed by the ROBINS-I showed that all included papers had a moderate overall risk-of-bias judgement 9,10,13,24,40,[42][43][44][45]55,[78][79][80][81][82][83][84][85][86] . Table 1 provides an overview of the quality of the evidence of the included papers, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Risk of bias as assessed by the RoB2 showed that all included papers had a low overall risk-of-bias judgement 47,[75][76][77] . Risk of bias as assessed by the ROBINS-I showed that all included papers had a moderate overall risk-of-bias judgement 9,10,13,24,40,[42][43][44][45]55,[78][79][80][81][82][83][84][85][86] . Table 1 provides an overview of the quality of the evidence of the included papers, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…49 Yet another study found that the duration of pain before iMCS surgery was of significant importance when it constituted >5 years, 29 whereas 1 study found no significant differences between responders and nonresponders to iMCS. 22 A more recent study from our group found that central lesions to respond more favorably to iMCS as compared with peripheral lesions, 28 which was agreed on in an expert meeting on iMCS. 34 However, none of these results were found to be of clinical importance in subsequent studies.…”
mentioning
confidence: 76%
“…A significant pain reduction as a response to a preoperative non-invasive rTMS test increases the probability of a good MCS therapeutic result [67]. However, since the available data is based on a limited number of patients, additional placebo-controlled, prospective clinical trials using neuronavigated rTMS are needed to manifest this relationship [13,68,69].…”
Section: Accuracy Of Rtms To Predict the Response Of Epidural Motor Cmentioning
confidence: 99%
“…DBS generally yields poor results in patients with chronic NP and is utilised only in a small subset of pain patients in whom other interventional methods have failed [8,11,12]. Although MCS has been demonstrated to produce significant pain reduction in subsets of patients with NP [13,14], the use of this technique has been hampered by difficulties to select the right patients, and to optimise and standardize stimulation parameters in order to achieve adequate, longterm pain relief [15][16][17].…”
Section: Introductionmentioning
confidence: 99%